DATA ANALYSIS ON INSTRUMENT SEPARATION DURING ENDODONTIC TREATMENT AND ITS MANAGEMENT - A RETROSPECTIVE STUDY - T, Aishuwariya.; Ramesh, Sindhu; Priscilla Antony, Delphine (International Journal of Psychosocial Rehabilitation, 2020)
Separation of endodontic instruments within the root canal is an unfortunate event. A separated instrument prevents complete debridement and sealing of the root canal system. Hence, every attempt must be made to retrieve the broken instrument. When instrument separation happens, it leaves the clinician in despair and anxiety and at last with a hope that non-surgical retreatment techniques would help in the removal of the instrument from the canal. The aim of this study was to analyze the different methods used for the management of the retrieval of broken instruments. This retrospective study was entirely based on data abstraction from existing records available at Saveetha Dental College, Chennai. Records of 95 patients were reviewed and analyzed. Out of these 14 patients who did not report for the follow-up visits,. Those were excluded from the study. A total of 81 cases were taken based on the inclusion and exclusion criteria. Out of which, 71% of cases were managed by obturating at the level of fracture, 22% of cases were retrieved, and in 18% of cases the instrument was bypassed. In this study, seven different parameters were checked, like the age, gender, sex, teeth type, type of instrument, and site and location of the instrument. Within the limitation of this study, it can be concluded that most of the cases were managed by obturating at the site of fracture, followed by a bypassing technique, later by retrieval using ultrasonics, manual methods like forceps, and a braided H-file technique.